Sialocele Post-trauma without Penetrating Injury (International Journal of Medical and Surgical Sciences, 2016)
Sialocele is a collection of saliva in the tissues surrounding the duct of the gland or parenchyma without proper drainage. The most common cause is the extravasation of saliva product to a disruption of the parenchyma or parotid duct secondary to a cutting trauma. If sialocele treatment is not performed in a timely manner it can generate an external fistula, facial scars and secondary infections. Male admitted to hospital with multiple facial fractures. After the reduction of edema, continued increased volume in the preauricular region localized, fluctuating, oval. The skin was asymptomatic, without secretions, with impairment of motor and sensory function in the right genial region. The aspiration of the increase in volume under a hypothesized hematoma was performed. After 2 days recurred. A tomography scan was requested and returned to realize the aspiration of which was sent to cytological exam. The diagnosis was post-trauma sialocele parotid and was performed emptying the contents and drainage type penrose intraoral. Was control the next day without relapses and the drain was removed after 2 months. It’s important to know that can generate a post-trauma sialocele without necessarily cutting trauma.